2023
DOI: 10.15406/jamb.2023.12.00351
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a formulated feed on the body growth and gonads quality of purple sea urchin (Paracentrotus lividus) aquaculture produced

Abstract: Sea urchin gonads are a prized gourmet product in many areas of the globe, and wild populations are threatened by increasing demand, making this species a very desirable product in aquaculture. Due to the unique needs of each stage of the life cycle, a viable food protocol that seeks to satisfy each stage while optimizing production profitability is required. The objective of this work was to test a formulated feed for sea urchins, through the analysis of somatic growth, gonad development and their fatty acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…and a food formulated for sea urchins. The choice of these two diets comes from previous knowledge of their potential influence on gonad development [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and a food formulated for sea urchins. The choice of these two diets comes from previous knowledge of their potential influence on gonad development [18].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of its fatty acid profile showed that the inert food had a higher content of the three types of fatty acids: saturated (SFA), monounsaturated (MUFA) and polyunsaturated (PUFA). The inert food had much higher levels of 22:6 ω3 (DHA) than the macroalgae, due to the enrichment of microalgae biomass (Schizochytrium), and a high content of this fatty acid was then found in the gonads of the sea urchins fed this food, showing the close relationship between the food supplied and the gonads [18].…”
Section: Gonadossomatic Indexmentioning
confidence: 99%
“…and a feed formulated for sea urchins. The choice of these two diets comes from previous knowledge of their potential influence on gonad development [18].…”
Section: Discussionmentioning
confidence: 99%
“…The inert diet (If) consisted of pellets formulated and produced by the company SPAROS, R&D (Olhão, Portugal), specifically for sea urchins. The nutritional characteristics are described in Araújo et al [18]. The sea urchins were fed once every 3-4 days based on a daily consumption for each urchin of 0.40 g of Ulva spp.…”
Section: Feedingmentioning
confidence: 99%
See 1 more Smart Citation